2005
DOI: 10.1111/j.1478-3231.2005.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplant immunosuppressive agents in non‐transplant chronic autoimmune hepatitis: the Canadian association for the study of liver (CASL) experience with mycophenolate mofetil and tacrolimus

Abstract: MMF is effective and well tolerated by patients with autoimmune hepatitis who do not respond to, or are intolerant of, conventional immunosuppressive agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
90
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 9 publications
3
90
0
Order By: Relevance
“…We recently completed a randomized controlled head-to-head comparison of low-dose cyclosporine with prednisolone for AIH induction therapy and found that low-dose cyclosporine is as effective as prednisolone, but less toxic (20). In addition to cyclosporine, other calcineurin inhibitors like tacrolimus (21,22) and purine antagonists like mycophenolate mofetil (21) have been used successfully to treat corticosteroid-resistant AIH patients. In a randomized controlled trial, budesonide has recently been shown to be as effective as prednisolone, with fewer side effects (23).…”
Section: Discussionmentioning
confidence: 99%
“…We recently completed a randomized controlled head-to-head comparison of low-dose cyclosporine with prednisolone for AIH induction therapy and found that low-dose cyclosporine is as effective as prednisolone, but less toxic (20). In addition to cyclosporine, other calcineurin inhibitors like tacrolimus (21,22) and purine antagonists like mycophenolate mofetil (21) have been used successfully to treat corticosteroid-resistant AIH patients. In a randomized controlled trial, budesonide has recently been shown to be as effective as prednisolone, with fewer side effects (23).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 These patients typically require indefinite therapy, and they remain at risk for drug toxicity and liver failure. The results of empiric treatment with ursodeoxycholic acid, 4 cyclosporine, 5,6 tacrolimus, 7,8 mycophenolate mofetil, [9][10][11][12] cyclophosphamide, 13 methotrexate, 14 rituximab, 15 budesonide, 16 intravenous globulin, 17 or leukocytopheresis 18 attest to the refractory nature of this condition.…”
mentioning
confidence: 99%
“…Eight (50%) had complete response, 2 (12.5%) had partial response, 4 (25%) had no response and 2 (12.5%) relapsed after 26.5 months follow-up. 23 Zachou and colleagues performed a prospective study in 59 patients assessing the efficacy of MMF as first line therapy in patients with AIH. Eighty eight percent (88%) of them responded to the combination of tapering dose of prednisolone and MMF 1-2 g/day within 3 months and the remaining patients responded eventually.…”
Section: Discussionmentioning
confidence: 99%